Face-to-Face Cognitive-Behavioral Therapy for Irritable Bowel Syndrome: The Effects on Gastrointestinal and Psychiatric Symptoms - Hanna Edebol-Carlman; Brjánn Ljótsson; Steven J. Linton; Katja Boersma; Martien Schrooten; Dirk Repsilber; Robert J. Brummer (Gastroenterology Research and Practice)
Irritable bowel syndrome (IBS) is a gastrointestinal disorder linked to disturbances in the gut-brain axis. Visceral hypersensitivity and pain are hallmarks of IBS and linked to the physiological and psychological burden and to the nonadaptive coping with stress. Cognitive-behavioral therapy (CBT) for IBS has proven effective in reducing gastrointestinal and psychiatric symptoms in IBS by means of coping with stress. The present pilot study evaluated for the first time whether CBT for IBS affected visceral sensitivity and pain. Individual CBT was performed for 12 weeks in 18 subjects with IBS and evaluated in terms of visceral sensitivity and pain during rectal distensions using the barostat method and self-rated visceral sensitivity and gastrointestinal and psychiatric symptoms. Visceral discomfort, urge, and pain induced by the barostat were not affected by CBT but were stable across the study. However, the level of self-rated visceral sensitivity and gastrointestinal and psychiatric symptoms decreased after the intervention. Central working mechanisms and increased ability to cope with IBS-symptoms are suggested to play a key role in the alleviation of IBS symptoms produced by CBT.